Rational Design of Drugs That Induce Human Immunodeficiency Virus Replication - Hamer, Dean H. (American Society for Microbiology, 2003)
Drugs that induce human immunodeficiency virus type 1 (HIV-1) replication could be used in combination with highly active antiretroviral therapy (HAART) to reduce the size of the latent reservoir that is in part responsible for viral persistence. Protein kinase C (PKC) is a logical target for such drugs because it activates HIV-1 transcription through multiple mechanisms. Here we show that HIV-1 gene expression can be induced by potent synthetic analogues of the lipid second messenger diacylglycerol (DAG) synthesized on a five-member ring platform that reduces the entropy of binding relative to that of the more flexible DAG template. By varying the alkyl side chains of these synthetic DAG lactones, it was possible to maximize their potency and ability to render latently infected T cells sensitive to killing by an anti-HIV-1 immunotoxin while minimizing the side effects of CD4 and CXCR4 downregulation and tumor necrosis factor alpha upregulation. The two lead compounds, LMC03 and LMC07, regulated a series of PKC-sensitive genes involved in T-cell activation and induced viral gene expression in peripheral blood mononuclear cells from HIV-1-infected individuals. These studies demonstrate the potential for the rational design of agents that, in conjunction with HAART and HIV-specific toxins, can be used to decrease or eliminate the pool of latently infected reservoirs by forcing viral expression.